2013
DOI: 10.1128/jb.02203-12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Two Polyhydroxyalkanoate Synthases in Bradyrhizobium japonicum USDA 110

Abstract: bBradyrhizobium japonicum USDA 110 has five polyhydroxyalkanoate (PHA) synthases (PhaC) annotated in its genome: bll4360 (phaC1), bll6073 (phaC2), blr3732 (phaC3), blr2885 (phaC4), and bll4548 (phaC5). All these proteins possess the catalytic triad and conserved amino acid residues of polyester synthases and are distributed into four different PhaC classes. We obtained mutants in each of these paralogs and analyzed phaC gene expression and PHA production in liquid cultures. Despite the genetic redundancy, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 56 publications
1
49
0
2
Order By: Relevance
“…Importantly, this observation is supported by the work of Miller and Tremblay (53), who showed that S. meliloti bacteroids from alfalfa nodules contain 34% of the total neutral lipid fraction as di-and triglycerides whereas these lipids were undetected in free-living S. meliloti. Moreover, the extraordinary deposition of PHB in bacteroids from common bean and soybean is an extreme example of carbon storage and redox balancing that has hitherto lacked a coherent explanation, particularly since preventing synthesis in these symbioses does not prevent N 2 fixation (19)(20)(21). Here we show that bacteroids of some strains of R. leguminosarum, such as Rlv3841, make PHB via a putative nifA-dependent type III PHB synthase.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Importantly, this observation is supported by the work of Miller and Tremblay (53), who showed that S. meliloti bacteroids from alfalfa nodules contain 34% of the total neutral lipid fraction as di-and triglycerides whereas these lipids were undetected in free-living S. meliloti. Moreover, the extraordinary deposition of PHB in bacteroids from common bean and soybean is an extreme example of carbon storage and redox balancing that has hitherto lacked a coherent explanation, particularly since preventing synthesis in these symbioses does not prevent N 2 fixation (19)(20)(21). Here we show that bacteroids of some strains of R. leguminosarum, such as Rlv3841, make PHB via a putative nifA-dependent type III PHB synthase.…”
Section: Discussionmentioning
confidence: 83%
“…apparently do not (18). While abolishing PHB synthesis does not adversely affect N 2 fixation rates in soybean and common bean (19)(20)(21), in Azorhizobium caulinodans, mutation of PHB synthase prevents N 2 fixation in both free-living and symbiotic forms (22), implying a fundamental role for PHB synthesis in at least some N 2 -fixing rhizobia.…”
mentioning
confidence: 99%
“…Cloning procedures, including DNA isolation, restriction digestion, ligation, and transformation, were performed as described previously (29). Tri-or biparental matings were performed with E. coli DH5␣ or S17-1 strains as described previously (3). Electroporation was performed with a Gene Pulser system (Bio-Rad, Hercules, CA) at 1.5 V, 25 F, and 200 ⍀ in a 0.1-cm-gap-width electroporation cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…However, this cycle of synthesis and degradation must be regulated because if the two pathways occur simultaneously (8), the net result would be consumption of energy and reducing power. The proteins involved in the different steps of the PHB cycle are well-characterized (9-12), and all of them are present in B. diazoefficiens (3,13,14); however, regulation of the cycle in this bacterium was not yet studied. In other rhizobium species, such as Rhizobium etli and Ensifer meliloti, the gene product of phaR (PHA [polyhydroxyalkanoate] regulator, previously known as aniA for anaerobically induced gene A) was reported to control, at least in part, PHB synthesis (15, 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation